2001
DOI: 10.1016/s0020-7292(01)00396-4
|View full text |Cite
|
Sign up to set email alerts
|

Non‐closure of visceral peritoneum at abdominal hysterectomy

Abstract: Our purpose was to determine whether non-closure of the visceral peritoneum alters post-operative outcome at abdominal hysterectomy. A prospective, randomized trial was performed. Of the 100 evaluable subjects, 50 had the visceral peritoneum left open whereas 50 were closed. Patients were observed for evidence of morbidity after the operation. Analysis of data was performed with use of the unpaired t-test for continuous variables. The visceral peritonization process at abdominal hysterectomy does not provide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Until the last decade of the twentieth century, visceral peritonealization after hysterectomy was a standard of care all Prospective randomized trials of hundreds of patients revealed that peritoneal closure at abdominal hysterectomy provides no immediate postoperative benefits while unnecessarily lengthening surgical time and anesthesia exposure and increasing blood loss. 1,2 Omission of peritoneal closure seems to be safe, as fever, infection, hemorrhage or revision are similar to peritonealization. 3,4,5 On the contrary, a significantly lower number of postoperative irregular pyelograms was reported in cases without peritoneal closure after radical hysterectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Until the last decade of the twentieth century, visceral peritonealization after hysterectomy was a standard of care all Prospective randomized trials of hundreds of patients revealed that peritoneal closure at abdominal hysterectomy provides no immediate postoperative benefits while unnecessarily lengthening surgical time and anesthesia exposure and increasing blood loss. 1,2 Omission of peritoneal closure seems to be safe, as fever, infection, hemorrhage or revision are similar to peritonealization. 3,4,5 On the contrary, a significantly lower number of postoperative irregular pyelograms was reported in cases without peritoneal closure after radical hysterectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior al cierre de la cúpula vaginal no se recomienda realizar un cierre peritoneal, ya que fisiológicamente reepiteliiza entre 48 y 72 horas, y no tendría un beneficio claro en disminuir la tasa de complicaciones postoperatorias, como adherencias, aparte de simplificar la técnica quirúrgica, disminuyendo así el tiempo operatorio (31)(32)(33) .…”
Section: Cierre De La Heridaunclassified
“…We identified three RCTs (n0298) comparing closure of the peritoneum with nonclosure in AH. While two trials evaluated either visceral [28] or parietal peritoneal closure [29], one studied the closure of both layers [30]. Nonclosure of the peritoneum, when compared with closure of either single layer or both layers, significantly reduced the operative time in all three trials.…”
Section: Moderatementioning
confidence: 99%
“…First, after reviewing over 3,000 abstracts, we identified only 19 RCTs [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] that met the inclusion criteria. These trials included 4,129 patients (Table 3).…”
Section: Commentsmentioning
confidence: 99%